Desarrollo del Departamento de Educación en Ciencias de la Salud en la Facultad de Medicina de la Universidad de Chile - Rosselot Jaramillo, Eduardo (Revista Hospital Clínico Universidad de Chile, 2009)
Practically, since it was born, an essential interest of the Faculty of Medicine of the University of Chile has been the continuous actualization of its learning objectives, and the education improvement of methodologies to teach and practice competences, therefore accomplishing advanced forming of professional resources, to cover every requirement in sanitary needs in the country. This has been a distinct seal, in the institutional history of the State University of the nation, that has been kept effectively radiating its action, from the more than two hundred years following its foundation age and early incorporation to the patron institution. The main stream orientation of its studies and advances has been, naturally, evolving; surging at the beginning, from the individual initiative of spontaneous academic leaders; thereafter from commended working groups or straight assessors to the executive authorities. Finally, starting the present century, the Department of Health Sciences Education was installed to guide advanced programs design to build the educational fortress needed by vocational selection of teachers, called from the same institution or coming for seemingly sake, from other universities in the country or foreign. The narrative and description of the evolution and actual standing of the Unit, its proposals, projects and perspectives, are offered concisely but thoroughly founded.